Habib Jafar's Thoughts on the Role of Moderate Religiosity in a Multicultural Society - Riadul Badiah Nurul Mubin; Fanika Saza; Nadziifah Hilda Herista; Anirmala Permata Sari; Intan Himmatul Aszka; Felia Nur Anggreani; Tri Nur Maulida (TATHO: International Journal of Islamic Thought and Sciences, 2026)
The aim of this qualitative study, conducted through media observation, is to explore the views of the Indonesian Muslim intellectual Habib Ja'far on the role of religious moderation in the context of multicultural society. The data consists of YouTube content presenting Habib Ja'far’s views. The research findings indicate that Habib Ja'far emphasises the implementation of indicators of religious moderation namely, national commitment, tolerance, non-violence, and adaptation to local culture with the messages he conveys being relevant in addressing issues of radicalism and intolerance, as well as fostering the creation of a healthy space for dialogue within society or among the younger generation. This research contributes to the assertion that religious moderation can serve as a strategic instrument in fostering social harmony within a multicultural society